The Concept of Maintaining Personal Reputation in Educational Institutions - Rejeki Urip , Sri; Kurniawati, Novi (KnE Social Sciences, 2020)
A reputable institution needs individuals who are able to maintain their personal reputation. This applies to all lecturers, education staff, and students. By maintaining a good personal reputation, the institution’s reputation will also be safeguarded. The objective of the study is to explore the concept of maintaining a good personal reputation from the perspective lecturers, education staff, and students of the Faculty of Language and Art, Universitas Negeri Semarang. Sources of data in this study came from lecturers and education staff in the faculty. The data was collected using a questionnaire which was then analyzed using a qualitative approach of Miles, Huberman, and Sadana. The results show that more than 89% of respondents at the Faculty of Languages and Arts agree and strongly agree to maintain their personal reputation. Most of them use WhatsApp that is equipped with group and status features that give everyone the opportunity to share what they feel and build their reputation. The use of language is also very important in efforts to maintain a personal reputation. Personal reputation is not something suddenly. This reputation is built through time. The statements of the respondent can be categorized via 6 elements consisting of (1) human capital, (2) time, (3) social control, (4) career success, (5) power, and (6) autonomy. Keywords: personal reputation, maintaining, lecturers, education